High scintillation yield and fast response to alpha particles from thin perovskite films deposited by pulsed laser deposition - Caricato, Anna Paola; Moretto, Sandra; Guascito, Maria Rachele; Quarta, Gianluca; Mazzeo, Marco; Favaro, Matteo; Rizwan Aziz, Muhammad; Provenzano, Chiara; Marra, Marcella; Cesaria, Maura; Polo, Matteo; Delgado, Jessica; et al. (Frontiers in Physics, 2022)
Although the field of solar cells is the most popular application of perovskite materials, various perovskites have been used in radiation detection applications for decades. The success of perovskites as radiation detectors rests partly on the same material properties that have led to other successful optoelectronics applications, meaning that other specific properties, like large stopping power, high mobility-lifetime product, fast response, large bulk resistance play a role. In this respect, all-inorganic perovskites are attracting a lot of attention as scintillator materials with performances sensitive to material shape (single crystals, nanocrystals, thin films) and growth methods. In this paper we report on the morphological, structural and optical response of thin CsPbBr3-based perovskite films, deposited by PLD and post-growth annealed at 350°C in air, following excitation by different particle sources. The annealing treatment resulted in a prompt structural refinement, grain growth and oxygen bonding to the Pb phase together with an enrichment of the surface in chemo-adsorbed oxygen probably due to Cs-O interactions, as evidenced by X-ray photoelectron spectroscopy. The film behaviour under 2MeV H+ ion beam irradiation at different fluences was analysed together with its scintillation properties following interaction with α particles from an Am-241 radioactive source demonstrating a very fast response for an inorganic material ( 5ns) and a photoelectron yield of about 47 % with respect to a commercial CsI:Tl scintillator.